HYGIENIC REQUIREMENTS FOR PHYSICAL EXERCISES (American Journal of Pedagogical and Educational Research, 2023)
As a result of many years of scientific research in the field of hygiene of physical education and sports, the main tasks of hygiene of physical exercises and sports have been determined: the study of the influence of environmental conditions on the health of those involved in physical culture and sports and their improvement; development of hygienic measures that promote the health of those involved in physical exercises and sports; increasing efficiency, endurance, ensuring the growth of sports achievements.